Optimalisasi Kesehatan Organ Reproduksi Wanita Melalui Senam “SI-EPIN” - Naomi Parmila Hesti Savitri; Sri Wahyuni (Barongko: Jurnal Ilmu Kesehatan, 2026)
ABSTRACT Reproductive health is a crucial aspect of a woman's quality of life. However, lack of physical activity, high stress levels, and an unbalanced diet often disrupt blood circulation and negatively impact uterine health. An effective non-pharmacological approach is the "Si-Epin" circulation and endorphin exercise. This community service activity aims to improve the knowledge and skills of women of childbearing age about "Si-Ephin" exercises as a way to prevent reproductive health problems. The activity was held at the X Village Hall, targeting 36 women of childbearing age. The activity included education, demonstrations, and practical practice of "Si-Ephin" exercises, which involve breathing exercises that stimulate blood circulation from the heart and stretching to stimulate endorphins. The results showed an increase in participants' understanding and skills regarding "Si-Ephin" exercises due to their ease of implementation. This activity is expected to contribute to maintaining reproductive health by reducing menstrual pain and smoothing the menstrual cycle. Keywords: Reproductive health, women's reproductive organs, women of childbearing age,"Si-Ephin" exercises ABSTRAK Kesehatan reproduksi merupakan aspek penting dalam kualitas hidup wanita. Namun, kurangnya aktivitas fisik, tingkat stress yang tinggi dan pola makan yang tidak seimbang sering kali mengganggu sirkulasi darah dan berdampak buruk pada kesehatan rahim. Upaya nonfarmakologis yang efektif adalah senam sirkulasi dan endorphin “Si-Epin”. Kegiatan pengabdian ini bertujuan untuk meningkatkan pengetahuan dan keterampilan Wanita Usia Subur tentang senam “Si-Ephin” sebagai upaya mencegah gangguan kesehatan reproduksi. Kegiatan dilaksanakan di Balai Desa X, dengan sasaran WUS sebanyak 36 orang. Metode kegiatan meliputi edukasi, demonstrasi, dan praktik senam “Si-Ephin” yang meliputi latihan pernapasan melalui sirkulasi pompa darah dari jantung dan peregangan untuk menstimulasi hormon endorphin. Hasil kegiatan menunjukkan peningkatan pemahaman dan keterampilan peserta mengenai senam “Si-Ephin” karena mudah dilakukan. Kegiatan ini diharapkan mempunyai kontribusi dalam menjaga kesehatan organ reproduksi untuk mengurangi nyeri menstruasi dan memperlancar siklus mentruasi. Kata Kunci: Kesehatan reproduksi, organ reproduksi wanita, Wanita Usia Subur, senam “Si-Ephin”